Strategies to improve diversity, equity, and inclusion in clinical trials. Issue 2 (8th September 2021) - Kahn, Justine M.; Gray, Darrell M.; Oliveri, Jill M.; Washington, Chasity M.; DeGraffinreid, Cecilia R.; Paskett, Electra D.
Abstract : There is a growing need for diversity, equity, and inclusion (DEI) in cancer care, particularly with respect to equal access and accrual to clinical trials. This commentary describe steps taken to address disparities in the authors' own clinical practice and proposes actions at the patient, provider, community, and institution levels to improve DEI in clinical trials.